Respread, mobilize and fragment the agenda: the secondary role of Telegram in the Spanish electoral campaign of November 2019 - Marcos-García, Silvia (2023)
Mobile instant messaging services, particularly Telegram, are becoming a new tool for politicians in their communication with citizens. This research aims to know the main functions attributed to Telegram, the themes of the messages and the multimedia resources used in the electoral campaign. We choose a descriptive study with an exploratory purpose and we apply quantitative content analysis to 877 messages published by the main Spanish parties during the November 2019 elections: PSOE, PP, Ciudadanos, Unidas Podemos, Izquierda Unida, Más País and Vox. The results show that the main political use of Telegram is to spread content from other redes sociales, especially Twitter and Facebook. This mobile application plays a secondary role in the communication strategy of the campaign parties. The function of participation and mobilization of the electorate also detects high values. Concerning the theme, the most recurrent topic in the content of the messages is vote and electoral results. Telegram also favours a high level of fragmentation of the political agenda. Additionally, we detected emergent use of innovative multimedia resources such as gifs, surveys and audios. Finally, we discover how the party's political history determines the use of this platform since traditional parties make more intensive use than emerging parties.